Mathourism di Keraton Sumenep Sebagai Pendekatan Baru dalam Sustainable Tourism Development: dalam Perspektif Pembelajaran - Hanik, Umi; Rahmawati, Ika Dian (Journal of Mathematics Education and Science, 2025)
This study explores the potential of mathourism at the Sumenep Palace as a new approach to sustainable tourism development, particularly from an educational perspective. The research was conducted using a library research method by analyzing various literature related to culture, architecture, tourism, and education. Sumenep Palace serves as a tangible example of cultural acculturation, representing diversity and harmony. These elements not only offer aesthetic value but also provide opportunities for integration into mathematics learning, especially in introducing geometric and symmetry concepts. Mathourism, which combines mathematics with culture-based tourism, aligns with the principles of sustainable tourism. This approach emphasizes cultural preservation, local community involvement, and experiential learning. Moreover, mathourism holds potential for empowering local communities through active participation in cultural preservation and the management of education-based tourist destinations. The results of the study indicate that the mathourism approach can support interdisciplinary learning that is relevant to real-life contexts while also enhancing the appeal of culture-based tourism at Sumenep Palace by integrating mathematical concepts with local cultural and historical contexts. This study is expected to serve as a foundation for further research, particularly in the development of mathourism-based learning modules and their implementation at other tourist destinations with similar cultural richness.